2005
DOI: 10.2174/1381612053764887
|View full text |Cite
|
Sign up to set email alerts
|

The Role of COX-2 in Oral Cancer Development, and Chemoprevention/ Treatment of Oral Cancer by Selective COX-2 Inhibitors

Abstract: Oral cancer is challenging for clinicians due to its high mortality and increasing incidence rate. Cyclooxygenase-2 (COX-2) is extensively expressed in oral cancer and oral premalignant lesions and seems to be enhanced specifically in high-risk oral lesions. Mounting evidence suggests that these inhibitors may represent a promising approach for chemoprevention or treatment of oral cancer. This review reports on Medline and PubMed literature searches of published articles from 1995 to 2003. Our purpose is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…Czerninski et al's findings further support targeting the mTOR pathway as a chemoprevention strategy. Other potential targets for chemoprevention besides mTOR (18) include AKT (14,19,20), cyclooxygenase-2, and EGFR (21,22). The overexpression and activation of these molecules in precancerous lesions and tumors in this mouse model suggests its usefulness for evaluating new drugs that modulate these targets.…”
mentioning
confidence: 99%
“…Czerninski et al's findings further support targeting the mTOR pathway as a chemoprevention strategy. Other potential targets for chemoprevention besides mTOR (18) include AKT (14,19,20), cyclooxygenase-2, and EGFR (21,22). The overexpression and activation of these molecules in precancerous lesions and tumors in this mouse model suggests its usefulness for evaluating new drugs that modulate these targets.…”
mentioning
confidence: 99%
“…In particular, abnormal expression ofCOX-2 has been supposed to be related to the pathogenesis of human cancer by affecting cell proliferation and apoptosis, angiogenesis and immune surveillance against cancer (2). On the basis of such molecular findings, more recent in vitro and epidemiologic studies focus on the putative role of non-steroidal anti-inflammatory drugs (NSAIDs), and in particular COX-2 inhibitors, as more selective and side-effect free anti-neoplastic, or even chemopreventive, agents (3)(4)(5).…”
mentioning
confidence: 99%
“…The incidence of oral cancer is increasing in many countries, and the lack of efficient therapy and the considerable associated morbidity and mortality make chemoprevention attractive (Goodin and Shiff, 2004;Wang, 2005), particularly since this might be targeted to high-risk individuals with leukoplakia or other precursor lesions (Nelson, 2006). NSAIDs have shown promise as chemopreventive agents for oral cancer in experimental studies (Goodin and Shiff, 2004), but the available epidemiologic data including the present analysis do not support a major protective effect of NSAIDs against oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have also consistently pointed to inverse associations between NSAID use and cancers of the stomach and oesophagus, whereas the results are mixed for other cancer sites (Gonzalez-Perez et al, 2003). Studies of animal models and human cancer cell lines have indicated that the potential chemopreventive effect of NSAIDs might extend to oral cancer (Goodin and Shiff, 2004;Wang, 2005), and this year a large phase III prevention trial of COX-2 inhibitors in patients with premalignant oral lesions (leukoplakia) is scheduled to be launched (Nelson, 2006). Interestingly, only a few epidemiological studies have provided data on the relationship between NSAID use and oral cancer, and the data are conflicting (Thun et al, 1993;Bosetti et al, 2003;Sørensen et al, 2003).…”
mentioning
confidence: 99%